The Effect of Tea (Camellia Sinensis) Consumption as a Chinese Cultural Practice on the Cognitive Function: A Quasi-Experimental Study - Kesaktian Manurung; Siska Evi Martina; Donal Nababan (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Cognitive decline is an increasing public health concern among older people, particularly those residing in nursing homes where structured preventive interventions are limited. Non-pharmacological approaches such as tea consumption have been associated with cognitive benefits; however, experimental evidence in institutionalized populations remains scarce. This study aims to examine the effect of structured daily tea (Camellia sinensis) consumption on cognitive function among older people in nursing homes in North Sumatra, Indonesia. A quasi-experimental design was conducted involving 60 participants aged 60–80 years, allocated into an intervention group (n = 30) and a control group (n = 30) using purposive sampling. The intervention group received 200 mL of supervised tea (Camellia sinensis) daily for four months, while the control group received a cognitive health information leaflet. Cognitive function was assessed using the Montreal Cognitive Assessment – Indonesian Version (MoCA-INA) at baseline and post-intervention. Data were analyzed using paired and independent t-tests. The intervention group showed a significant improvement in cognitive scores from 17.60 ± 4.32 to 21.93 ± 4.03 (p < 0.001), with a large within-group effect size (Cohen’s d =1.04). Post-intervention cognitive scores were significantly higher in the intervention group compared to the control group (p < 0.001), indicating a large between-group effect (Cohen’s d = 1.20). Structured tea (Camellia sinensis) consumption may represent a culturally relevant, low-cost strategy to support cognitive health among institutionalized older people. Further randomized controlled trials with longer follow-up are warranted Keywords: Dementia, Older People, Cognitive Function, Tea Consumption, Nursing Home